2008
DOI: 10.1093/pasj/60.5.1133
|View full text |Cite
|
Sign up to set email alerts
|

Suzaku Observation of the Ophiuchus Galaxy Cluster: One of the Hottest Cool Core Clusters

Abstract: We present the analysis of a Suzaku observation of the Ophiuchus galaxy cluster. We confirmed that the cluster has a cool core. While the temperature of the intracluster medium (ICM) decreases toward the center, the metal abundance increases. Except for the core (r < ∼ 50 kpc), the cluster is hot (∼ 9-10 keV) and is almost isothermal for r < ∼ 1 Mpc; the latter contradicts a previous study. We do not detect the variation of the redshift of the ICM in the cluster; the upper limit of the velocity difference is 3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
53
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 77 publications
(80 reference statements)
13
53
0
Order By: Relevance
“…Similar results were reported in the Suzaku analysis of Ophiuchus (Fujita et al 2008). We also found that the modelling of the soft X-ray sky background using ROSAT All Sky Survey data close to Ophiuchus yielded a higher value NH = 0.46 × 10 22 cm −2 (Sect.…”
Section: Nhsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar results were reported in the Suzaku analysis of Ophiuchus (Fujita et al 2008). We also found that the modelling of the soft X-ray sky background using ROSAT All Sky Survey data close to Ophiuchus yielded a higher value NH = 0.46 × 10 22 cm −2 (Sect.…”
Section: Nhsupporting
confidence: 90%
“…Suzaku analysis of Ophiuchus suggested that Ophiuchus has a cool core (Fujita et al 2008). The typical cooling radius of 70 kpc (=2 arcmin) found in a cluster sample by the Chandra satellite (Vikhlinin et al 2006) is also consistent with the extent of the central excess.…”
Section: Cool Corementioning
confidence: 59%
“…Suzaku data (Fujita et al 2008b) indicate that this cluster has a cool, dense core. We recently found at the cluster center a low surface brightness diffuse emission that it is classified has a mini-halo Murgia et al 2009Murgia et al , 2010b.…”
Section: Ophiuchusmentioning
confidence: 91%
“…Suzaku data (Fujita et al 2008) and the archival Chandra data indicate that this hot cluster has a cool, dense core. The archival wide-field ROSAT PSPC image suggests an ongoing unequal-mass merger, but the Chandra image indicates that the core is still largely undisturbed, although it exhibits the prototypical cold fronts caused by gas sloshing (Ascasibar & Markevitch 2006).…”
Section: Ophiuchusmentioning
confidence: 93%